Untying Surface Chemistry and Emulsion Stability to Construct Multifunctional Pickering Emulsion SERS Sensors for Pretreatment‐Free Quantitative Analysis in Bio‐Media - Yingrui Zhang; Chunchun Li; Ruairi Carland; Ziwei Ye; Steven E. J. Bell; Yikai Xu (Advanced Science)
Abstract Plasmonic Pickering emulsions have immense potential as enhancing substrates in surface‐enhanced Raman spectroscopy (SERS). Traditionally, the functional nanoparticles also act as the emulsion stabilizer, so that their surface chemistry is tied directly to emulsion stability. However, this has meant that adsorption of molecules to the plasmonic nanoparticles destabilizes the emulsion system, which severely limits the use of Pickering emulsions in SERS. Here, we used a dual‐particle approach to create plasmonic Pickering emulsions, in which emulsion stability is maintained solely by one type of nanoparticle so that the other could be used to provide functionality without constraints to its surface properties. This allowed us to construct multiwalled carbon nanotubes‐Au@Prussian blue Pickering emulsion SERS sensors with integrated internal standards and filtration functionalities, which enabled quantitative, biphasic and multiplex analysis of discrete molecules in serum. The synthetic approach used in this work can be readily extended to form Pickering emulsions carrying functional components with arbitrary surface functionalities, which paves the way for advanced applications in sustainability and healthcare.